Boosting Efficiency: Integrating Inventory Apps in Accounting Information Systems - Romy Rahwani, Noor; Sadewa, Manik Mutiara; Nikmah, Nailiya; Mukhlisah, Nurul; Iriawan, Sandra (P3M Politeknik Negeri Banjarmasin, 2023)
This research explored the implications of computer-based Accounting Information Systems (AIS) in the realm of inventory transactions, aiming to enhance business efficiency through the integration of business processes within companies. While prior research had primarily focused on transitioning from manual to computerized systems, this study shifted the focus towards comprehensive integration, addressing inefficiencies such as transaction redundancies, manual handovers, and potential data inaccuracies. Employing the Software Development Life Cycle (SDLC), the research methodology emphasized analysis, design, and implementation stages. The analysis stage involved identifying gaps in existing literature, while the design stage developed document flowcharts for inventory transactions with and without integration. The implementation stage provided a technical overview of integrating the designed flowcharts using recommended software. The findings revealed that the majority of prior studies endorsed the transition to computerized systems but fell short in addressing business process integration. The proposed integration framework was demonstrated through document flowcharts, showcasing the effectiveness of computer-based AIS in minimizing inefficiencies. The study illustrated a reduction in transaction redundancies and manual handovers, leading to enhanced business efficiency, data accuracy, and consistency. In conclusion, this study advocated for a holistic approach in leveraging technology for accounting practices. It underscored the significance of integrating various functions within businesses, going beyond mere automation. The practical implementation of integration features through off-the-shelf software solutions provided actionable insights for companies seeking to optimize their business processes in the digital era